Assessment of Physical, Chemical, Microbiological, and Sensory Characteristics of Global and Local Cola Carbonated Soft Drink Brands in Egypt - Helal, Mohamed Mahmoud; El-Adawy, Tarek Ahmed; El-Beltagy, Alaa Ahmed; El-Bedawey, Aboelfatah A; Youssef, Saad Michael (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2023)
This study aimed to estimate the physical, chemical, microbiological, and sensory characteristics of commercial cola-carbonated soft drink brands in the Egyptian market to evaluate the safety of these drinks. Two commercial drinks brands, global and local cola, were used in the study. Physico-chemical, microbiological, and sensory characteristics of cola soft drinks were affected (p ≤0.05) by the cola brand. The global cola soft drink had higher (p ≤0.05) physicochemical characteristics than the local cola soft drink after production and for 6 months storage period. In addition, the Global cola soft drink brand had a higher percentage of taste, odour, appearance, and overall acceptability than the local cola soft drink brand by 20%, 22.53%, 12.42%, and 18.55%, respectively, after production. Gradual (p ≤0.05) decline in all sensory scores was detected for 6-month storage period. The global cola soft drink had a much lower total bacterial count (2.3 CFU.100 ml-1) than a local cola soft drink (123 CFU.100 ml-1). Thus, local brands of cola consumption after production could have public health risks due to high microbial load and deteriorated product shelf life. Also, quality control during processing and public health awareness could mitigate risk. During the 6-month storage period, the total bacterial count was completely absent after 3 and 4 months for global and local cola soft drinks, respectively. The global and local cola soft drink brands during the storage period at room temperature for 6 months were completely free of aciduric bacteria, coliform bacteria, and Escherichia coli, yeast, and mould as well. The results indicate that the physico-chemical attributes of all tested carbonated soft drinks samples (global & local) are within the European guidelines for carbonated soft drinks but are not compatible with the label of the reported bottle. Also, local brands of cola consumption after production could have public health risks due to high microbial load and deteriorated product shelf life.